Langkah-Langkah Utama dalam Pencegahan Korupsi Membangun Integritas dan Transparansi di Masyarakat - Angelica Valentina (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
Corruption is a major issue hindering the development of society and the economy in Indonesia. This study discusses the key steps in preventing corruption by emphasizing the importance of building integrity and transparency within the community. Through interviews with various individuals, insights were gained regarding public perceptions of corruption and the measures that can be taken to mitigate it. The findings indicate that education, the instillation of honesty values, and active community participation are crucial in creating an environment free from corruption. This research aims to contribute to the efforts in combating corruption in Indonesia.